PENGETAHUAN DAN PERILAKU DETEKSI DINI KANKER SERVIKS - Arlien Jeannete Manoppo (Klabat Journal of Nursing, 2022)
Good knowledge about cervical cancer can lead to an understanding for the individual so that it moves his behavior to prevention, namely early detection through visual inspection of acetic acid (IVA). The purpose of this study was to determine the relationship between the level of knowledge and the behavior of early detection of IVA in women of childbearing age. The research design used is the descriptive correlation with a cross-sectional approach. Respondents in the study amounted to 146 who were determined using the purposive sampling technique. The results of this study are the majority of women of childbearing age (25-49 years) have a sufficient level of knowledge of 91 (62.3%) and do not carry out early detection of IVA examination 114 (78.1%), and the results of the chi-square analysis show that there is a significant relationship. significant with a low correlation between knowledge level and behavior of IVA early detection examination in women of childbearing age in a positive direction (r=0.308; p=0.000). This research can be continued by adding demographic data of respondents, such as education level and age of respondents. KEYWORDS: Behavior Early Detection Of Acetic Acid Visual Inspection, Cervical Cancer, Knowledge Pengetahuan yang baik mengenai kanker serviks dapat menimbulkan pemahaman bagi individu tersebut sehingga menggerakan perilakunya untuk melakukan pencegahan, yaitu deteksi dini melalui pemeriksaan inspeksi visual asam asetat (IVA). Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat pengetahuan dengan perilaku pemeriksaan deteksi dini IVA pada wanita usia subur. Desain penelitian yang digunakan adalah deskriptif korelasi dengan pendekatan cross sectional. Responden dalam penelitian berjumlah 146 yang ditentukan menggunakan teknik purposive sampling. Hasil penelitian ini adalah mayoritas wanita usia subur (25-49 tahun) memiliki tingkat pengetahuan cukup 91 (62,3 %) dan tidak melakukan deteksi dini pemeriksaan IVA 114 (78,1%), serta dari hasil analisis chisquare menunjukkan bahwa terdapat hubungan yang signifikan dengan korelasi rendah antara tingkat pengetahuan dan perilaku pemeriksaan deteksi dini Iva pada wanita usia subur dengan arah yang positif (r=0,308; p=0,000). Penelitian ini dapat diteruskan dengan menambahkan data demografi responden, seperti tingkat pendidikan dan juga usia responden. KATA KUNCI: Kanker serviks, Pengetahuan, Perilaku Deteksi Dini Inspeksi Visual Asam Asetat